The incorrectness in assessment procedure of creditworthiness - Nowak, Paweł (Journal of Finance and Financial Law, 2017)
The correct assessment of consumer credit ability is in interest of creditor and debtor and also increase stability of financial system. The article point out the major incorrectness in assessment of creditworthiness, occurring both on consumer and bank side. There are low safety buffer of bank rates, low costs of living, excessive period of credit, failure in information delivery and hidden information by consumers. The text includes the set of corrective and repair actions also, being at disposal of banks and consumer which increase efficiency of consumer credit ability assessment.